Ultrasmall Ruthenium Nanoparticles with Boosted Antioxidant Activity Upregulate Regulatory T Cells for Highly Efficient Liver Injury Therapy. Issue 29 (24th June 2022) - Xia, Fan; Hu, Xi; Zhang, Bo; Wang, Xun; Guan, Yunan; Lin, Peihua; Ma, Zhiyuan; Sheng, Jianpeng; Ling, Daishun; Li, Fangyuan
Abstract: Nanozymes exhibiting antioxidant activity are beneficial for the treatment of oxidative stress‐associated diseases. Ruthenium nanoparticles (RuNPs) with multiple enzyme‐like activities have attracted growing attention, but the relatively low antioxidant enzyme‐like activities hinder their practical biomedical applications. Here, a size regulation strategy is presented to significantly boost the antioxidant enzyme‐like activities of RuNPs. It is found that as the size of RuNPs decreases to ≈2.0 nm (sRuNP), the surface‐oxidized Ru atoms become dominant, thus possessing an unprecedentedly boosted antioxidant activity as compared to medium‐sized (≈3.9 nm) or large‐sized counterparts (≈5.9 nm) that are mainly composed of surface metallic Ru atoms. Notably, based on their antioxidant enzyme‐like activities and ultrasmall size, sRuNP can not only sustainably ameliorate oxidative stress but also upregulate regulatory T cells in late‐stage acetaminophen (APAP)‐induced liver injury (ALI). Consequently, sRuNPs perform highly efficient therapeutic efficiency on ALI mice even when treated at 6 h after APAP intoxication. This strategy is insightful for tuning the catalytic performances of nanozymes for their extensive biomedical applications. Abstract : By tuning the size of ruthenium nanoparticles (RuNPs) from 5.9 to 2.0 nm, the dominated surface composition changes from metallic Ru to oxidized Ru, resulting in the superior antioxidant activity of small‐sized RuNPs (sRuNP) than their larger counterparts. Subsequently, sRuNP can sustainably alleviate oxidative stress and increase the frequency of regulatory T cells for highly efficient liver injury therapy.